Ab Initio Study on the Aromaticity of All-Metallic Anion $La^{2-}_4$ (Journal of Atomic and Molecular Sciences, 2014)
We extended the aromaticity concept to all-metallic anion $La^{2-}_4$ and thenperformed Ab intio calculations (B3LYP/LANL2DZ, B3PW91/LANL2DZ andMP2/LANL2DZ) on the selected structures. The computed results indicate that anion $La^{2-}_4$ has two stable isomers: one is the bidentate $C_{2v}$ structure and another is the squareplanar $D_{4h}$ structure. The further analysis on energies shows that the square planar $D_{4h}$ structure is more stable than the bidentate $C_{2v}$ structure. The computed nucleus-independentchemical shifts (NICS) on the most stable $D_{4h}$ structure show that thesquare planar $La^{2-}_4$ ring exhibits higher degree of aromaticity. The detailed MOs analysisfurther reveals that the square planar $La^{2-}_4$ ring possesses four independent delocalizedbonding systems, each has two electrons satisfying the $4n + 2$ electron countingrule of aromaticity, suggesting that these species have four-fold aromaticity.
Keywords: ab initio study; aromaticity; magnetic susceptibilities; nucleus-independent chemical shift (NICS).